TEACHERS IN TIMES OF PANDEMIC: WHAT ARE WE REALIZING? - Orlowski, Nelem; Mocrosky, Luciane Ferreira [UNESP]; Bicudo, Maria Aparecida Viggiani [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2022)
In this text, we expose a study guided by the question: what is this, educating in the pandemic in social isolation? We focus on the account of the experience of a teacher from the Municipal Education Network, working in the early years of elementary school, amid the determinants arising from the pandemic caused by SARS-CoV-2. Supported by a reading-of-practice analysis, in a phenomenological qualitative approach, we explain understandings about the respondent, showing that the phenomenon of educating-in-a-pandemic-in-social-isolation was shown by distant remote teaching, possible to be modified by decisions teachers to be together with their peers, in which the technological possibilities can reestablish and strengthen human bonds capable of sustaining the continuity of teaching. We conclude by highlighting the urgency of presence and the technological approach for the return to human proximity as a way in which each one takes responsibility, acts and launches himself to seek understandings addressed to the future.
PROFESSORAS EM TEMPOS DE PANDEMIA: DO QUE ESTAMOS NOS DANDO CONTA?
Keywords: Mathematical Education; Pandemic SARS-CoV-2; Phenomenology; Practice readings; Remote teaching